Cellular oxygen consumption in patients with diabetic ketoacidosis - Jacob Vine; John H. Lee; Lakshman Balaji; Anne V. Grossestreuer; Andrea Morton; Natia Peradze; Nivedha Antony; Noa Berlin; Max S. Kravitz; Shannon B. Leland; Katherine Berg; Ari Moskowitz; et al. (Intensive Care Medicine Experimental)
Abstract Background Diabetic ketoacidosis (DKA) is a potentially life-threatening disorder associated with severe alterations in metabolism and acid–base status. Mitochondrial dysfunction is associated with diabetes and its complications. Thiamine and coenzyme Q10 (CoQ10) are important factors in aerobic metabolism. In this study, we measured cellular oxygen consumption rates (OCRs) and the effects of in vitro administration of thiamine and CoQ10 on OCRs in patients with DKA versus healthy controls. Methods Blood samples were collected from a prospective cohort of patients with DKA and from controls. Cellular OCRs were measured in peripheral blood mononuclear cells (PBMC) without treatment and after treatment with thiamine, CoQ10, or both. The mitochondrial profile was measured using an XFe96 Extracellular Flux Analyzer and XF Cell Mito Stress Test Kit (Seahorse Bioscience). A linear quantile mixed model was used to compare OCRs and estimate treatment effects. Results A total of 62 patients with DKA and 48 controls were included in the study. The median basal and maximal OCRs were lower in the DKA group than in the control group (basal: 4.7 [IQR: 3.3, 7.9] vs. 7.9 [5.0, 9.5], p = 0.036; maximal: 16.4 [9.5, 28.1] vs. 31.5 [20.6, 46.0] pmol/min/µg protein, p < 0.001). In DKA samples, basal and maximal OCRs were significantly increased when treated with thiamine, CoQ10, or both. In controls, basal and maximal OCR were significantly increased only with thiamine treatment. Conclusion Mitochondrial metabolic profiles of patients with DKA demonstrated lower cellular oxygen consumption when compared to healthy controls. Oxygen consumption increased significantly in cells of patients with DKA treated with thiamine or CoQ10. These results suggest that thiamine and CoQ10 could potentially have therapeutic benefits in DKA via their metabolic effects on mitochondrial cellular respiration.